Phase I Trials of Anti-ENPP3 Antibody–Drug Conjugates in Advanced Refractory Renal Cell Carcinomas - Thompson, John A.; Motzer, Robert J.; Molina, Ana M.; Choueiri, Toni K.; Heath, Elisabeth I.; Redman, Bruce G.; Sangha, Randeep S.; Ernst, D. Scott; Pili, Roberto; Kim, Stella K.; Reyno, Leonard; Wiseman, Aya; et al. (Clinical Cancer Research, 2018)
Purpose: To determine the safety, pharmacokinetics, and recommended phase II dose of an antibody–drug conjugate (ADC) targeting ectonucleotide phosphodiesterases-pyrophosphatase 3 (ENPP3) conjugated to monomethyl auristatin F (MMAF) in subjects with advanced metastatic renal cell carcinoma (mRCC). Patients and Methods: Two phase I studies were conducted sequentially with 2 ADCs considered equivalent, hybridoma-derived AGS-16M8F and Chinese hamster ovary–derived AGS-16C3F. AGS-16M8F was administered intravenously every 3 weeks at 5 dose levels ranging from 0.6 to 4.8 mg/kg until unacceptable toxicity or progression. The study was terminated before reaching the MTD. A second study with AGS-16C3F started with the AGS-16M8F bridging dose of 4.8 mg/kg given every 3 weeks. Results: The AGS-16M8F study (n = 26) closed before reaching the MTD. The median duration of treatment was 12 weeks (1.7–83 weeks). One subject had durable partial response (PR; 83 weeks) and 1 subject had prolonged stable disease (48 weeks). In the AGS-16C3F study (n = 34), the protocol-defined MTD was 3.6 mg/kg, but this was not tolerated in multiple doses. Reversible keratopathy was dose limiting and required multiple dose deescalations. The 1.8 mg/kg dose was determined to be safe and was associated with clinically relevant signs of antitumor response. Three of 13 subjects at 1.8 mg/kg had durable PRs (range, 100–143 weeks). Eight subjects at 2.7 mg/kg and 1.8 mg/kg had disease control >37 weeks (37.5–141 weeks). Conclusions: AGS-16C3F was tolerated and had durable antitumor activity at 1.8 mg/kg every 3 weeks. Clin Cancer Res; 24(18); 4399–406. ©2018 AACR.